1998
DOI: 10.1152/ajprenal.1998.274.3.f611
|View full text |Cite
|
Sign up to set email alerts
|

Localization of the extracellular Ca2+/polyvalent cation-sensing protein in rat kidney

Abstract: We previously identified transcripts encoding a G protein-coupled, extracellular calcium/polyvalent cation-sensing receptor, RaKCaR, in rat kidney (D. Riccardi, J. Park, W.-S. Lee, G. Gamba, E. M. Brown, and S. C. Hebert. Proc. Natl. Acad. Sci. USA 92: 131–135, 1994), which was proposed to provide the mechanism for modulating a variety of renal functions in response to changes in extracellular Ca2+ (E. M. Brown. In: Handbook of Physiology. Bethesda, MD: Am. Physiol. Soc., 1992, sect. 8, vol. 2, chapt. 39, p. 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
238
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(257 citation statements)
references
References 25 publications
18
238
0
1
Order By: Relevance
“…We cannot exclude that the lower SBP in our animals played a role in attenuating progression of renal failure, but such near normalization of BP had not been observed in a previous study (9) suggesting that the significant effect of low PTH is at least not fully explained by differences in BP. The calcium sensing receptor is expressed by various types of renal cells (45)(46)(47), but similar changes were seen in R-568 treated and PTX animals; it is therefore unlikely that a direct action of R-568 on the calcium sensing receptor played a role in the beneficial effect on progression observed in the present study. It is noteworthy that we observed no effects of R-568 or 5% dietary calcium supplement on BP in rats with normal renal function (unpublished data).…”
Section: Discussionsupporting
confidence: 64%
“…We cannot exclude that the lower SBP in our animals played a role in attenuating progression of renal failure, but such near normalization of BP had not been observed in a previous study (9) suggesting that the significant effect of low PTH is at least not fully explained by differences in BP. The calcium sensing receptor is expressed by various types of renal cells (45)(46)(47), but similar changes were seen in R-568 treated and PTX animals; it is therefore unlikely that a direct action of R-568 on the calcium sensing receptor played a role in the beneficial effect on progression observed in the present study. It is noteworthy that we observed no effects of R-568 or 5% dietary calcium supplement on BP in rats with normal renal function (unpublished data).…”
Section: Discussionsupporting
confidence: 64%
“…In addition, the elevation of divalent cations in the basal compartment may inhibit calcium transport via PCLN-1. The extracellular calcium/polyvalent cation-sensing protein is expressed in the basal membrane of epithelial cells in the proximal tubule, TAL, and distal tubule (28). It has been reported that the elevation of either basal calcium or magnesium decreases the reabsorption of calcium and magnesium in TAL (29).…”
Section: Discussionmentioning
confidence: 99%
“…Under physiological conditions, the increased serum Ca 2+ levels stimulate this receptor and decrease the active reabsorption of Na + . This reduces the luminal positive driving force and results in increased urinary Ca excretion [171]. Activation of the CaSR can disrupt electrolyte transport via inhibition of four different pathways: (1) renal channel proteins, such as the Na-K-2Cl cotransporter (NKCC2), (2) ROMK, (3) Na + /K + -ATPase, and (4) paracellular diffusion [146].…”
Section: Aminoglycosidesmentioning
confidence: 99%